THE ANALYSIS OF SEMIOTIC SIGNS IN THE NUDES EYE SHADOW PALETTE ADVERTISEMENT BY MAYBELLINE NEW YORK - I Gusti Agung Ayu Sania Pradnyanita; Desak Putu Eka Pratiwi; Putu Nur Ayomi (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
Language is something that we use to communicate with others. The function of language has an important role in addressing people’s intent or purpose. Thus, the use of language should be right and fit with the situation and the goal to do. In doing the communication, some people would be delivering their message explicitly. But some of them deliver the message implicitly, they tend to use signs and symbols. One of the studies that talked about the meaning of the language in a certain sign is semiotic. Semiotic is the study that discusses the signs, which signs are divided into verbal and visual signs. The purpose of this study is to investigate the verbal and visual signs and the meaning itself in the advertisement this research is needed because some of the advertisers put the message behind their advertiser, which means that the message is not only delivered explicitly. The method used in this study is a qualitative method. The data utilized in this study were taken from YouTube. To investigate the information, this review utilized the theory of Semiotic by Saussure (1983), the theory of meaning from Barthes (1976), and the supporting theory of color by Cerrato (2012). The analyst tracked down 8 verbal signs and 9 visual signs.